PENGEMBANGAN MEDIA BAGAN POHON TERHADAP HASIL BELAJAR SISWA KELAS V DI SEKOLAH DASAR - angga putra; Putri Surya Damayanti; Ija Srirahmawati; Sri Purnawati (Jurnal Holistika, 2022)
This research is motivated by the lack of effective use of media in learning activities so that students are less effective in understanding the material, researchers offer the development of new media, namely tree chart media that is in accordance with the concrete operational stage in order to have a direct influence on students. The tree chart media is a complete medium that has branches, stems, and leaves, each of which facilitates or has meaning based on the learning material to be studied. The purpose of this study was to test the validity, practicality and effectiveness of the tree chart media on the learning outcomes of fifth grade students of SDN 17 Woja. This study uses research and development methods (Research and Development) which refers to the four D (4-D) model. Data collection techniques in this study were questionnaires, interviews, observations, tests, and documentation. Data analysis techniques in this study include media validity analysis, media practicality analysis and media effectiveness analysis. The results of the recapitulation of the validity of the learning media from two experts were 83% with the "Valid" category. The results of the recapitulation of the practicality of the tree chart media obtained a percentage of 95.5% with a very practical category. Recapitulation of students' cognitive learning outcomes with a classical completeness score of 83%. The test of students' affective learning outcomes, there are 3 students who fall into the "very good" category with a percentage of 13%, 14 students who fall into the "good" category with a percentage of 61%, 3 students who fall into the fairly good category with a percentage of 13%, and 3 students are included in the “Need Guidance” category with a percentage of 13%. Psychomotor learning outcomes, it is known that there are 16 students' psychomotor results in the "Good" category with a percentage of 70% and 7 students in the "good enough" category with a percentage of 30%.Keywords: Development, Tree Media, Learning Outcomes